Baksan large volume scintillation telescope: a current status. (February 2020) - Petkov, V B; Fazliakhmetov, A N; Gangapshev, A M; Gavrin, V N; Ibragimova, T V; Kochkarov, M M; Kazalov, V V; Kudrin, D Yu; Kuzminov, V V; Lubsandorzhiev, B K; Malyshkin, Yu M; Novikova, G Ya; et al.
Abstract: A current status of the project of a large volume scintillation telescope at the Baksan neutrino observatory is presented. The main research activities of the BLVST are low- energy neutrino physics, astrophysics and geophysics. To detect geoneutrinos, large-scale new- generation scintillator detectors located at large depths in the regions with a low background level from nuclear reactors are required. The Baksan Neutrino Observatory is geographically located in one of these places. Recently resumed R&D activities are aimed at the creation of new-generation telescope with a target mass of 10 kt at a depth of 4800 m.w.e. A small scale prototype is already under construction.